Klasifikasi Tingkat Keberhasilan Produksi Ayam Broiler di Riau Menggunakan Algoritma C4.5 - Muhammad Rifaldo Al Magribi; Alwis Nazir; Siska Kurnia Gusti; Lestari Handayani; Iwan Iskandar (JURIKOM (Jurnal Riset Komputer), 2023)
Broiler chicken farming is one sector that contributes to playing an important role in causing an increase in the quality of life of the community, especially in fulfilling animal protein. Broiler chicken is a superior breed that has high meat productivity and a short reproductive cycle, thus encouraging the formation of partnerships between breeders and large companies. As the core, the company evaluates the success of breeders as seen from the performance index or IP value. The attributes that affect the IP value are depletion, average harvest weight, feed conversion ratio (FCR), and harvest age. The purpose of this research is to find out the attributes that most influence the success rate of broiler production in Riau and to get the accuracy value of the decision tree model using the C4.5 algorithm. This study used 952 livestock production data in Riau divided by a ratio of 80% training data and 20% test data. This test produces a decision tree in which the FCR attribute is the root node with a gain value of 0.45 and is the attribute that most influences the success rate of broiler chicken production in Riau. Evaluation using the confusion matrix produces an accuracy value of 97.11%, a precision of 98.89%, a recall of 98.16%.